2022
DOI: 10.1208/s12249-022-02241-9
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluations of Berberine-Loaded Microparticles Filled In-House 3D Printed Hollow Capsular Device for Improved Oral Bioavailability

Abstract: The low oral bioavailability, short biological half-life, high dose, and frequent dosing of berberine (BBR) contribute to its restricted clinical use despite its extensive pharmacological activity. Thus, the objective of this study was to formulate sustained-release microparticles (MPs) using a pH-independent release polymer and to evaluate their potential to improve the oral bioavailability of BBR. BBR loaded MPs were prepared using the emulsion crosslinking method and evaluated for particle size, circularity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Other in vivo and in vitro studies revealed that berberine‐loaded microparticles filled in‐house 3D printed hollow capsular (AUC value: 99.629 ng/ml*h) have higher oral bioavailability in comparison with the pristine berberine (AUC value: 28.629 ng/ml*h); (Choudhury et al, 2022). In rats, using berberine‐loaded liposomes at a dose of 100 mg/kg resulted in even 628% enhancement in the oral bioavailability compared to pure berberine (Duong et al, 2022).…”
Section: Pharmacokinetic Parametersmentioning
confidence: 96%
See 3 more Smart Citations
“…Other in vivo and in vitro studies revealed that berberine‐loaded microparticles filled in‐house 3D printed hollow capsular (AUC value: 99.629 ng/ml*h) have higher oral bioavailability in comparison with the pristine berberine (AUC value: 28.629 ng/ml*h); (Choudhury et al, 2022). In rats, using berberine‐loaded liposomes at a dose of 100 mg/kg resulted in even 628% enhancement in the oral bioavailability compared to pure berberine (Duong et al, 2022).…”
Section: Pharmacokinetic Parametersmentioning
confidence: 96%
“…28.629 ng/ml*h); (Choudhury et al, 2022). In rats, using berberineloaded liposomes at a dose of 100 mg/kg resulted in even 628% enhancement in the oral bioavailability compared to pure berberine (Duong et al, 2022).…”
Section: "Bioavailability and Anti-diabetic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic polymer B. Natural polymer  Synthetic polymers  Non-biodegradable polymers: polymethyl methacrylate (PMMA), acrolein, glycidol Methacrylate, epoxy polymer  Biodegradable polymers: lactides, their glycosides and their copolymers, polyalkylenes Cyanoacrylate, polyanhydride  B.Natural polymers It is obtained from different sources such as proteins, carbohydrates and chemically modified products.carbohydrates  Proteins: albumin, gelatin and collagen, carbohydrates: agarose, carrageenan, chitosan, starch, chemicals  .Modified carbohydrates: poly (acrylic acid) dextran, poly (acrylic acid) starch [3].  Particle size and shape: laser microscopy, scanning electron microscopy  Electron spectroscopy for chemical analysis: determination of surface chemistry  Attenuated Total Reflection Fourier Transform Infrared Spectroscopy: Determination of Degradation  Catch rate: % catch = actual content/theoretical content × 100  Thermal Analysis: Differential Scanning Calorimetry (DSC)  Swelling index: Characterization of microspheres using the swelling index technique  METHOD: Take another solution (100ml) such as (distilled water, buffer solution with pH value (1.2,4.5, 7.4) Take alginate microspheres (100mg) and place them in a wire basket.…”
Section: Introductionmentioning
confidence: 99%